2015
DOI: 10.1017/s1368980015000695
|View full text |Cite
|
Sign up to set email alerts
|

Factors within the family environment such as parents’ dietary habits and fruit and vegetable availability have the greatest influence on fruit and vegetable consumption by Polish children

Abstract: Objective: To identify determinants of fruit and vegetable (F&V) consumption among school-aged children. Design: A survey study was conducted in October 2010. The questionnaire contained questions concerning social and demographic data, lifestyle and dietary habits, particularly the frequency of F&V consumption, availability of F&V and knowledge about recommended amounts of F&V intake. Setting: Polish primary schools. Subjects: Children (n 1255) aged 9 years from randomly selected primary schools and their par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 27 publications
2
38
0
1
Order By: Relevance
“…The present study also shows maternal education is positively associated with fruit intake and total fruit and/or vegetable intake. This agrees in part with the findings of a Polish study [39], which found parental education influenced fruit, but not vegetable, consumption. Mothers educated to a higher level are more likely to pay attention to healthy dietary habits and contribute to fruit and vegetable consumption, particularly fruit consumption, because children readily eat fruits, fruit preparation is easier, and fruit is a well-known healthy dietary component [39].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study also shows maternal education is positively associated with fruit intake and total fruit and/or vegetable intake. This agrees in part with the findings of a Polish study [39], which found parental education influenced fruit, but not vegetable, consumption. Mothers educated to a higher level are more likely to pay attention to healthy dietary habits and contribute to fruit and vegetable consumption, particularly fruit consumption, because children readily eat fruits, fruit preparation is easier, and fruit is a well-known healthy dietary component [39].…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that home availability of fruit and vegetable is the most important determinant of fruit and vegetable consumption among children [1820212223373940] due to a direct effect on fruit and vegetable consumption and the indirect effects of parental example [41]. One study conducted in Iceland reported fruit and vegetable availability at home seems to be a more important determinant of vegetable consumption by children than of fruit consumption [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this intervention the proportion of school children who reported having the support of their parents to achieve the consumption of vegetables and fruits in school increased; it has been found in other studies that parental encouragement can influence their children to consume V&F, providing them the food and continually encouraging them to consume them (25), so interventions aimed at promoting the consumption of vegetables and fruits in children must train parents and help them prepare more attractive dishes for their children.…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, a sibling study where exposure to the environment - such as lifestyle - was similar showed that there was no difference in BMI between siblings exposed versus those unexposed to GDM in utero [75]. These results suggest that the environmental influence of lifestyle habits has a stronger influence than intrauterine exposure to GDM in the development of obesity in children, because siblings generally have similar lifestyle habits [75,76,77]. …”
Section: Dietary Intake and Physical Activity During Childhoodmentioning
confidence: 99%